Childhood Trauma And Social Support Predicting Relationship Satisfaction Among Adult Samples - Enyelunekpo R. Roberts; Comfort S. Atota; Ekaette N. Ufeh; Emmanuel E. Uye (International Journal of Economics, Business and Innovation Research, 2026)
Childhood trauma and social support are two critical constructs that significantly shape adult emotional health and interpersonal relationships. While studies have used different predictors to examine relationship satisfaction among different populations and samples, one group that has been understudy especially in the Nigerian setting is the young adults. Therefore, this study examines the predictive roles of childhood trauma and social support on relationship satisfaction among young adults in Port Harcourt, Rivers State, Nigeria. The study adopted cross-sectional survey design while purposive sampling technique was used to select youth samples from five communities. Data were conveniently collected from 278 participants using validated questionnaires and analyzed using multiple regression to test one hypothesis which was accepted at p = .001 level of significance. The result revealed that childhood trauma and social support jointly predicted relationship satisfaction among study participants, R2 = .248, F (2,275) = 31.56, p=.001. Furthermore, the result indicated childhood trauma (β = .243, t = 2.74, p = .007) and social support (β = .328, t = 3.73, p =.001) independently predicted relationship satisfaction among study participants. The study concludes that childhood trauma and social support are robust predictors of relationship satisfaction among young adults in the Port Harcourt metropolis. The study recommends that parents should foster nurturing and supportive environments and actively build and maintain strong social support networks that would help them cope with challenges and enhance their relationship satisfaction.